Pengaruh Integritas, Komunikasi dan Budaya Organisasi terhadap Kinerja Karyawan pada PT. Gajah Putih Lestari, Banda Aceh - Endang Sumardi; Sonny Hersona GW; Nunung Nurhasanah (Universitas Batanghari, 2022)
This study became carried out to research the have an impact on of integrity, communique and organizational way of life on employee overall performance at PT. Gajah Putih Lestari, Banda Aceh. This research makes use of quantitative strategies with descriptive and verification methods. The sample on this examine were ninety five human beings as employees of PT. Gaja Putih Lestari Banda Aceh using the Slovin technique in figuring out the pattern. The validity of the facts accomplished consisted of validity and reliability tests and classical assumption tests together with normality, multicollinearity, and heteroscedasticity checks. The statistics evaluation approach used is the size variety approach, with more than one regression analysis with the help of research equipment the usage of SPSS model 25.primarily based on the analysis that has been completed, the variables of integrity, verbal exchange, organizational lifestyle and worker performance have a small suggest price in comparison to the same old deviation, which means that each variable has a small exchange. From the results of SPSS information processing version 25. The correlation coefficient between the integrity and verbal exchange variables is 0.814, the organizational culture variable and employee performance is 0.252. which means that that the variable of integrity with verbal exchange has a very strong have an impact on, while the variable of organizational way of life and worker overall performance has a very small impact. The partial effect of the integrity variable on worker overall performance is 0.109 with a sig price of 0.1/2 extra than 0.05, so integrity has no high quality and tremendous impact on employee overall performance. The have an impact on of the communique variable on worker overall performance is zero.127 with a sig price of 0.029, that's smaller than 0.05, because of this that verbal exchange has a wonderful effect on employee performance. The partial impact of organizational subculture on employee overall performance is zero.167 with a sig value of zero.027, which is smaller than zero.05, this means that that organizational lifestyle has a positive and full-size effect on worker overall performance. The simultaneous impact of the variables of integrity, communique and organizational lifestyle on worker performance has a sig value of zero.003 that's smaller than zero.05, which means that that the variables of integrity, verbal exchange and organizational subculture have a big impact on employee performance.